2020
DOI: 10.1371/journal.ppat.1008871
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that immunization with TP0751, a bipartite Treponema pallidum lipoprotein with an intrinsically disordered region and lipocalin fold, fails to protect in the rabbit model of experimental syphilis

Abstract: Deconvolution of syphilis pathogenesis and selection of candidate syphilis vaccinogens requires detailed knowledge of the molecular architecture of the Treponema pallidum outer membrane (OM). The T. pallidum OM contains a low density of integral OM proteins, while the spirochete's many lipoprotein immunogens are periplasmic. TP0751, a lipoprotein with a lipocalin fold, is reportedly a surface-exposed protease/adhesin and protective antigen. The rapid expansion of calycin/lipocalin structures in the RCSB PDB da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 134 publications
5
36
0
Order By: Relevance
“…Because T. pallidum is an extracellular bacterium (6,8), an effective vaccine must elicit antibodies against antigens on the bacterial surface (105,145). Years of investigation of the molecular architecture of the T. pallidum outer membrane have shown that the principal candidates for syphilis vaccine design are contained within the spirochete's OMPeome (6,11,108,137). The structural models described herein provide investigators, for the first time, with a platform for a rational, systematic investigation of the combination of OMPs needed to elicit long-lived protection.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Because T. pallidum is an extracellular bacterium (6,8), an effective vaccine must elicit antibodies against antigens on the bacterial surface (105,145). Years of investigation of the molecular architecture of the T. pallidum outer membrane have shown that the principal candidates for syphilis vaccine design are contained within the spirochete's OMPeome (6,11,108,137). The structural models described herein provide investigators, for the first time, with a platform for a rational, systematic investigation of the combination of OMPs needed to elicit long-lived protection.…”
Section: Downloaded Frommentioning
confidence: 99%
“…In association with T. pallidum Tp0750, which contains a Von Willebrand factor type A domain, it has been reported to promote fibrinolysis and ECM degradation ( Houston et al., 2012 ; Houston et al., 2014 ). However, leptolysin is secreted extracellularly whereas pallilysin was recently shown to reside within the periplasmic space ( Luthra et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…TP0856 and TP0858 were expressed in E. coli Overexpress C41(DE3) ( 5 ). Cells were centrifuged at 6,000 × g for 15 min at 4°C, resuspended in buffer (50 mM Tris [pH 7.5], 50 mM NaCl) containing 100 μg of lysozyme and protease inhibitors, lysed by sonication, and then centrifuged at 20,000 × g for 30 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%